2016
DOI: 10.1007/s11250-016-1070-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of three tropical forage legumes and their influence on growth performance, carcass traits and organ weights of pigs

Abstract: The effects of tropical forage legumes on feed intake, growth performance and carcass traits were investigated in 16 groups of two Large White × Duroc pigs. The diets consisted of a commercial corn-soybean meal diet as the basal diet and three forage-supplemented diets. Four groups of control pigs received daily 4 % of body weight of the basal diet, and 12 groups of experimental pigs were fed the basal diet at 3.2 % of body weight completed with fresh leaves of one of the three forage legumes (Psophocarpus sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…us, as cowpea is a good source of protein and own reasonable digestible energy, it can be a good supplement to feed livestock under subsistence farming systems of the region. However, the nutrient content and indicators of feed intake and digestibility of genotypes at present were inferior to some of the previous findings elsewhere in the tropical areas [20,21].…”
Section: Discussioncontrasting
confidence: 99%
“…us, as cowpea is a good source of protein and own reasonable digestible energy, it can be a good supplement to feed livestock under subsistence farming systems of the region. However, the nutrient content and indicators of feed intake and digestibility of genotypes at present were inferior to some of the previous findings elsewhere in the tropical areas [20,21].…”
Section: Discussioncontrasting
confidence: 99%
“…The nutrient composition of legume trees varies with species, soil condition, season, and stage of leaf growth (Nyamukanza & Scogings, 2008), harvesting and post-harvesting techniques and/or conditions. Earlier reports revealed that leguminous leaf meals are a good source of protein for pigs (Halimani et al, 2005;Khanyile et al, 2014;Ndou et al, 2015;Kambashi et al, 2016). Knowledge on chemical composition and physical properties of leguminous leaf meals is relevant in designing formulation strategies to ensure that anti-nutritional factors do not constrain pig performance.…”
Section: Indigenous Legume Plants In Southern Africamentioning
confidence: 99%
“…The response of pigs to incorporation of leguminous leaf meal cannot be generalised because it depends on different characteristics of chemical composition and physical properties of leaf meal including the ratio of the different components in the overall diet The variation in average daily feed intake (ADFI), average daily gain (ADG), feed conversion ratio (FCR) and gain: ratio (G\F) could be due to different leguminous species, stage of harvesting, harvesting method and pig genotypes used (Table 4). Maximum utilisation of leaf meals is limited because of the presence of polyphnolic compounds, which plays a major role in reduction in intake, reduced digestibility and lower efficiency (Bhat et al, 2013;Kambashi et al, 2016). The low FCR is driven by bitter and astringent taste from tannins.…”
Section: Performance Of Pigs Fed On Leguminous Leaf Mealsmentioning
confidence: 99%
See 2 more Smart Citations